Comparison of the Benefits of Moringa Leaves and Orange in Increasing Hemoglobin Levels in Pregnant Women - Nuryati Nuryati; Ninik Indayani (Global Health Science Group, 2023)
Anemia has a negative impact even in all cycles of pregnancy to childbirth such as: bleeding, difficulty fighting infection, premature birth and even increasing the risk of fetal death. Many non-pharmacological therapies that can scientifically increase haemoglobin levels include Moringa leaves and oranges. The purpose of this study was to determine the effect of Moringa leaf cooking water and sweet orange juice on hemoglobin levels of pregnant women with anemia. This research is a type of intervention research with experimental quasy design. The location used for this research is in the working area of the Lightning Health Center in June 2023. The sample used in this study used a total sampling of 30 pregnant women who would be divided into 2 groups, namely 15 pregnant women with Moringa leaf water and 15 pregnant women with orange juice. Analysis of the difference test with the independent t test and the difference test between the two groups with the Wilcoxon signed rank test. The results of the independent T test where the pair Pretest intervention and posttest intervention group Moringa leaves and squeezed oranges showed Sig.2-tailed values of 0.000 < 0.05.